Institutional Quality, Financial Stability, and FDI Dynamics in Asia - Diana Wijayanti; Rindang Nuri Isnaini Nugrohowati (Economics Development Analysis Journal, 2025)
This study aims to analyze how institutional quality and financial stability influence foreign direct investment (FDI) in Asian countries, examining differences across country income groups. This study utilizes data from 39 Asian countries spanning the years 2013 to 2021. The analytical tool used is the Generalized Method of Moments (GMM), consisting of first-difference GMM and system GMM. Furthermore, this study uses principal component analysis (PCA) to calculate composite variables related to the institutional quality index. The results show that institutional quality and financial stability have a positive overall impact on FDI in Asian countries. However, the impact varies depending on the country's level of income. Institutional quality has a more significant impact in high-income countries, while in lower-middle-income countries, economic growth is the primary determinant of FDI. These findings emphasize the importance of improving governance and financial stability in attracting foreign investment. Governments, particularly in lower-middle-income countries, need to strengthen law enforcement, reduce corruption, maintain political stability, and create regulations that support an investment climate to make it more attractive to foreign investors